The Influence of Values on Adolescents’ Problem Behavior - HOU, Yongmei; Jiangmin, Zheng (Advances in Social Sciences Research Journal, 2022)
Objective To explore the present status of adolescents’ values and problem behavior, and to analyze the impact of values on adolescents’ problem behavior. Methods A stratified random sampling was used to select 893 adolescents. They were investigated with the Chinese Adolescent Values Questionnaire (CAVQ) and the 2001-Chinese-Version of Youth Self-Report and Profile (YSＲP-2001-CV). Results ⑴ The scores of the two dimensions of fashion trend and enjoyment of happiness of CAVQ were greater than 2.5 and less than 3.5, belonging to the middle level. The scores of the other six dimensions of CAVQ were greater than 3.5, belonging to high scores. ⑵ The scores of the two factors of YSＲP-2001-CV were less than 1.5, which belong to low scores. ⑶ Multiple linear stepwise regression analysis showed that the scores of social equality and fashion trend positively predicted the total score of YSＲP-2001-CV (β=.297, .318, all P <.001). The scores of collective orientation, discipline compliance, family affection, peer friendship and surpassing and enterprising negatively predicted the total score of YSＲP-2001-CV (β=-.237 to -.408, all P <.001). Conclusion teenagers’ values have not been established, and their problem behavior is obvious. Values may be an important influencing factor of teenagers’ problem behavior.